2023
DOI: 10.1002/uog.26042
|View full text |Cite
|
Sign up to set email alerts
|

Effect of bariatric surgery on maternal cardiovascular system

Abstract: Objective Bariatric surgery is a successful treatment for sustainable weight loss and has been associated with improvement in cardiovascular function. Pregnancy after bariatric surgery is becoming increasingly common; however, little is known about the maternal cardiovascular system postsurgery. The aim of this study was to investigate maternal cardiovascular adaptation to pregnancy in women with previous bariatric surgery, compared with that in women with no history of weight‐loss surgery and an early‐pregnan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“…[ 110 ] When post-bariatric pregnant women were compared, longitudinally, to pregnant women without surgery but with early pregnancy BMI similar to the pre-surgery BMI of the post-bariatric women (n=30 in each group), we found that the former group had more favourable haemodynamic indices, diastolic and systolic function and altered cardiac geometry with lower LV mass and RWT. [ 111 ] It is conceivable that the cardiac changes observed in pregnant women with previous bariatric surgery may contribute to the lower prevalence of hypertensive disorders seen in this population.…”
Section: Bariatric Surgerymentioning
confidence: 99%
“…[ 110 ] When post-bariatric pregnant women were compared, longitudinally, to pregnant women without surgery but with early pregnancy BMI similar to the pre-surgery BMI of the post-bariatric women (n=30 in each group), we found that the former group had more favourable haemodynamic indices, diastolic and systolic function and altered cardiac geometry with lower LV mass and RWT. [ 111 ] It is conceivable that the cardiac changes observed in pregnant women with previous bariatric surgery may contribute to the lower prevalence of hypertensive disorders seen in this population.…”
Section: Bariatric Surgerymentioning
confidence: 99%